Proportion of US Hospitalized Medically Ill Patients Who May Qualify for Extended Thromboprophylaxis - Miao, Benjamin (Clin Appl Thromb Hemost, 2019)
Extended thromboprophylaxis with oral anticoagulation can reduce the risk of symptomatic venous thromboembolism (VTE) in high-risk patients. We sought to estimate the proportion of medically ill patients in the United States who might qualify for extended thromboprophylaxis according to the criteria used in the Medically-Ill Patient Assessment of Rivaroxaban versus Placebo in Reducing Post-Discharge Venous ThromboEmbolism Risk (MARINER) trial. We analyzed 2014 National Inpatient Sample (NIS) data that provide a 20% weighted annual sample of all discharges from US acute-care hospitals. Hospitalizations for acute medically ill patients were identified as those with a primary discharge diagnosis code for heart or respiratory failure, ischemic stroke, infection, or inflammatory diseases. Patients were excluded if they were <40 years old, admitted for surgery or trauma, had a length of stay <3- or >35-days, or were contraindicated to nonvitamin K antagonist oral anticoagulants. The modified International Medical Prevention Registry on Venous Thromboembolism (IMPROVE)-VTE score was used to stratify patients’ risk for postdischarge VTE, with a score of 2 to 3 suggesting patients were at moderate- and ≥4 as high-risk. Of the 35 358 810 hospitalizations in the 2014 NIS, 1 849 535 were medically ill patients admitted for heart failure (10.1%), respiratory failure (12.2%), ischemic stroke (8.8%), infection (58.5%), or inflammatory diseases (10.4%). The modified IMPROVE-VTE score classified 1 186 475 (64.1%) of these hospitalizations as occurring in moderate-risk and 407 095 (22.0%) in high-risk patients. This real-world study suggests a substantial proportion of acute medically ill patients might benefit from extended thromboprophylaxis using the modified IMPROVE-VTE score and clinical elements of the MARINER trial.